Transection of the anterior tibial artery during minimally invasive plate osteosynthesis of the proximal tibia. (April 2017) - Katsuura, Yoshihiro; Gardner, Warren E.
Abstract: Minimally invasive plate osteosynthesis (MIPO) techniques have been developed to protect the blood flow to tissues surrounding fractures and reduce the risk of non-union. Typically, MIPO involves the insertion of a plate through a small incision and fixation with percutaneously applied screws targeted fluoroscopically. Here we present a case of a transected anterior tibial artery during routine minimally invasive plate osteosynthesis of a tibial plateau fracture to highlight a rare complication of this type of surgery and discuss relevant anatomical considerations. Level of evidence: According to the OCEBM Levels of Evidence Working Group, this study is graded as a Level of Evidence IV.